Penerapan Metode Balance ScoreCard Untuk Penentuan Key Performance Indicator di Departemen Production Engineering Pada PT XYZ - Sulkhan Sulkhan; Alek Alek (SEED: Journal of Scientific Research, 2025)
This study determined Key Performance Indicators (KPI) using four Balanced Scorecard perspectives to improve the performance appraisal system in the Production Engineering department of a pharmaceutical company in Tangerang. The Balanced Scorecard is a management tool for implementing strategy and measuring performance using four perspectives. These KPIs serve as an effective performance measurement tool for organizations and managers in providing annual performance appraisals for all employees aligned with the organization's vision, mission, and strategy.The total balanced score resulted in an A score of 0.915, based on the grade system (>0.90 ~ 1.00). The patrol achievement and maintenance performance KPI indicators achieved 100% of their targets.